High-activity ultrafine powder and preparation method thereof

By grinding silicon residue, limestone, slag, and modified agent at a certain proportion, and combined with modified treatment and surface modification, preparation of high -active ultra -fine powder, solving the problem of decline in material performance in existing technology, solved the problem of decline in material performance in existing technology It realizes high stability and heat resistance under the acid -base environment and high temperature conditions.

CN119371128APending Publication Date: 2025-01-28YUNNAN SUYUAN NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411503352.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

It is difficult to effectively prepare ultrafine powders with high activity in the prior art, especially in acid-base environments and high temperature conditions, the material properties are prone to decline.

Method used

By grinding silicon residue, limestone, slag, and modifiers according to a certain proportion, combined with the modifiers of the N-phenyl-3-amino propyl tritenide, the alkaline liquid etching, and the coupling agent The surface modification is prepared for high -active ultra -fine powder, and powder grinding through the excitation effect of composite stimulants to improve its activity and comprehensive performance.

Benefits of technology

It improves the heat resistance of ultra -fine powder in the stability and high temperature conditions in the acid -base environment, and enhances its physical and chemical properties, such as strength, hardness and color stability, and is suitable for a variety of industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005103156340000111
    Figure BDA0005103156340000111
Patent Text Reader

Abstract

The invention relates to the technical field of ultrafine powder, in particular to high-activity ultrafine powder and a preparation method thereof.Siliceous slag, limestone, slag and a modifier are compounded, the interaction and synergistic effect among different raw materials can be improved, and the stability of the high-activity ultrafine powder in an acid-base environment is improved; the performance reduction caused by chemical reaction is reduced; by introducing N-phenyl-3-aminopropyltrimethoxysilane, a stable organic silicon layer can be formed on the surface of the micro-powder, oxygen permeation at high temperature can be effectively blocked, the thermal oxidative degradation process of the material can be delayed, and the modified micro-powder can still keep good physical and chemical properties under the high-temperature condition; such as strength, hardness and color stability, and is suitable for application in a high-temperature environment; the alkali liquor etching treatment increases the roughness of the surface of the micro powder, provides more reaction sites and adsorption areas, and is beneficial to adhesion and reaction of a subsequent modifier.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ultrafine powders, and in particular to a high-activity ultrafine powder and a preparation method thereof. Background Art

[0002] In the field of materials science, ultrafine powders have shown great potential in multiple industrial applications due to their unique physical and chemical properties. In particular, silicon powder and slag powder, as two important inorganic non-metallic mineral materials, the preparation technology of their highly active ultrafine powders has always been a research hotspot.

[0003] Silica powder is mainly obtained by a series of processing from siliceous raw materials such as quartz sand. It has excellent chemical stability, high heat resistance, high insulation and good filling properties. With the advancement of science and technology and the improvement of environmental protection requirements, the preparation technology of silica powder has been continuously improved and optimized. For example, a comprehensive method (such as mechanochemical method, physical and chemical method) is used to combine the advantages of physical and chemical methods to prepare high-purity, narrow particle size distribution, high-activity silica powder through multiple steps. The surface modification of silica powder, such as the use of silane coupling agents, can further improve its dispersibility, compatibility and activity, and broaden its application field. Slag powder, especially blast furnace slag powder, is a by-product produced in the steel industry. After grinding, it has excellent volcanic ash activity and potential water hardness. In order to improve the activity and performance of slag powder, grinding aids are added during the grinding process to improve the surface charge and dispersibility of slag.

[0004] In summary, as two important inorganic non-metallic mineral materials, the preparation technology of highly active ultrafine powders of silicon micropowder and slag micropowder is of great significance for improving material properties and broadening application fields. Summary of the invention

[0005] Technical issues solved

[0006] In view of the above-mentioned shortcomings of the prior art, the present invention provides a high-activity ultrafine powder and a preparation method thereof, aiming to prepare ultrafine powder with higher activity.

[0007] Technical Solution

[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0009] A method for preparing highly active ultrafine powder, the preparation method comprising:

[0010] S1, mixing siliceous slag, limestone, slag and a modifier in a certain proportion and grinding them to prepare a highly active ultrafine powder, wherein the modifier is sodium sulfate;

[0011] S2, modifying the highly active ultrafine powder with N-phenyl-3-aminopropyltrimethoxysilane to prepare heat-resistant modified micropowder;

[0012] S3, firstly etching the surface of the high-activity ultrafine powder with an alkali solution, and then modifying the surface of the high-activity ultrafine powder with a silane coupling agent KH-570 to prepare an activated modified micropowder;

[0013] S4, then using the sodium aluminate solution as a raw material to prepare ultrafine aluminum hydroxide powder;

[0014] S5, weigh 50 parts by weight of heat-resistant modified micropowder, 50 parts by weight of activated modified micropowder, 30 parts by weight of ultrafine aluminum hydroxide micropowder and 25 parts by weight of composite activator, mix them, place them in a blast drying oven at 105° C. and dry them for 2 hours, and record the result as powder component;

[0015] S6. Pour the powder components into a vibration mill at a material-to-ball ratio of 1:12 and grind for 10-30 minutes. The obtained powder is a highly active ultrafine powder after passing through a 400-mesh sieve.

[0016] Furthermore, the preparation method of the highly active ultrafine powder in S1 is:

[0017] Siliceous slag, limestone, slag and sodium sulfate are weighed in a weight ratio of 3:1:2:1 for later use; the slag in the above weight proportion is poured into a crusher and crushed to a particle size of less than 5 mm; then, the slag is mixed with siliceous slag, limestone and sodium sulfate in the above weight ratio and poured into a ball mill together; after ball milling for 30 minutes, a highly active ultrafine powder is obtained; the crusher model is a 5E-JC100×60 jaw crusher, and the ball mill model is an SM-500 ball mill.

[0018] Furthermore, the preparation steps of the heat-resistant modified micropowder in S2 are:

[0019] Step 1, weigh 12-15g of the dried high-activity ultrafine powder and disperse it in 200mL of ethanol aqueous solution, add 0.2g of N-phenyl-3-aminopropyltrimethoxysilane dropwise after ultrasonic treatment, and stir and disperse to obtain the component to be reacted;

[0020] Step 2: Place the components to be reacted in a constant temperature water bath at 80°C and stir to react for 1 hour. After the reaction is completed, place them in a vacuum drying oven at 80°C and dry them for 24 hours to obtain heat-resistant modified micropowder.

[0021] Furthermore, the drying method in step 1 is to place the mixture in a vacuum drying oven at 120° C. and dry it for 2 hours, the volume fraction of the ethanol aqueous solution in step 1 is 90%, the ultrasonic treatment method in step 1 is to ultrasonically disperse the mixture at a frequency of 26 kHz for 30 minutes, the stirring and dispersing method in step 1 is to stir the mixture at a speed of 500 r / min for 5 minutes, and the stirring reaction speed in step 2 is 300 r / min.

[0022] Furthermore, the preparation steps of the activated modified micropowder in S3 are:

[0023] Step A, immersing the highly active ultrafine powder in a sodium hydroxide solution for 24-48 hours for etching, filtering out the filtrate, washing with deionized water and anhydrous ethanol three times respectively, filtering and drying, and the obtained powder is recorded as etching micropowder;

[0024] Step B: Mix 200 mL of deionized water and 300 mL of methanol, add 3-4 g of silane coupling agent KH-570, stir for hydrolysis, add 25-30 g of etching powder, stir and react at room temperature for 12 hours, filter to remove the filtrate, wash with deionized water and anhydrous ethanol three times each, and dry to obtain the activated modified powder.

[0025] Furthermore, the concentration of the sodium hydroxide solution in step A is 5 mol / L, the drying method in step A is to place it in a vacuum drying oven at 105°C and dry it for 2 hours, the stirring and hydrolysis method in step B is to stir at a speed of 300 r / min for 20 minutes, the stirring reaction speed in step B is 200 r / min, and the drying method in step B is to place it in a vacuum drying oven at 105°C and dry it for 2 hours.

[0026] Furthermore, the preparation steps of the ultrafine aluminum hydroxide powder in S4 are:

[0027] Step I: Add 15-20 g of lime to 200 mL of sodium aluminate solution, stir thoroughly, let stand at 97 ° C for 4 hours, filter and record as refined solution, heat the refined solution to 20 ° C and simmer at 230 m 3 / h ventilation of carbon dioxide gas until the pH value of the refined solution reaches 8.5-10, then stop ventilation, and let it stand for 24h to age, the obtained product is recorded as high-activity seed crystal;

[0028] Step II: Add 5 g of highly active seed crystals to 20 mL of refined solution heated to 55°C, stir and decompose at a speed of 220 r / min for 2 hours, then add 80 mL of refined solution and heat to 55°C, continue stirring at the original speed for 8 hours, then filter, wash the filter cake with deionized water at a temperature of 45°C until it is neutral, and obtain ultrafine aluminum hydroxide powder after drying.

[0029] Furthermore, the mass fraction of the sodium aluminate solution in step I and step II is 10%, the operation method of fully stirring in step I is stirring at a speed of 400 r / min for 30 minutes, and the operation method of drying in step II is placing it in a vacuum drying oven at 85° C. for 2 hours.

[0030] Furthermore, the preparation method of the composite activator in S5 is to mix quicklime, hemihydrate gypsum, natural gypsum and water glass in equal weight ratios, and the filling rate of the vibration mill in the grinding process of S6 is 40%.

[0031] A high-activity ultrafine powder is prepared by a high-activity ultrafine powder preparation method.

[0032] Beneficial Effects

[0033] The present invention provides a highly active ultrafine powder and a preparation method thereof. Compared with the prior art, the present invention has the following beneficial effects:

[0034] 1. The present invention uses siliceous slag, limestone, slag and modifier for compounding, which can improve the interaction and synergistic effect between different raw materials, so that the stability of high-activity ultrafine powder in acid-base environment is improved, and the performance degradation caused by chemical reaction is reduced; the introduction of N-phenyl-3-aminopropyltrimethoxysilane can form a stable organic silicon layer on the surface of the micropowder, which can effectively block the oxygen penetration at high temperature and delay the thermal oxidation degradation process of the material, so that the modified micropowder can still maintain good physical and chemical properties such as strength, hardness and color stability under high temperature conditions, and is suitable for application in high temperature environment; secondly, the alkali solution etching treatment in the present invention increases the roughness of the micropowder surface, provides more reaction sites and adsorption area, which is conducive to the attachment and reaction of the subsequent modifier, and the modification effect of the silane coupling agent KH-570 can not only reduce the interaction force between the micropowder particles, improve its dispersion uniformity in the solvent or matrix, but also improve the activity of the micropowder.

[0035] 2. The ultrafine aluminum hydroxide powder prepared by the present invention has a small particle size and uniform distribution, and has a higher specific surface area and surface activity. The ultrafine particle size makes the aluminum hydroxide powder show higher activity and reaction rate in chemical reactions, which is beneficial to its application in the fields of catalysts, adsorbents, etc. The ultrafine aluminum hydroxide powder, heat-resistant modified powder and activated modified powder are compounded in a specified ratio and ground under the stimulation of a composite stimulant, which can make the prepared ultrafine powder have higher activity and significantly improve the comprehensive performance of the prepared ultrafine powder, such as strength, toughness, heat resistance, weather resistance, etc.; secondly, the addition of waste slag in the preparation of ultrafine powder in the present invention can play a role in waste recycling, and reasonable process design and waste treatment measures can reduce the generation and emission of waste, thereby reducing pollution to the environment and achieving energy-saving and environmental protection effects. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] The present invention will be further described below in conjunction with the embodiments.

[0038] Example 1

[0039] A method for preparing a highly active ultrafine powder in this embodiment is as follows:

[0040] S1, mixing siliceous slag, limestone, slag and sodium sulfate in a certain proportion and grinding them to prepare a highly active ultrafine powder;

[0041] Wherein, the preparation method of highly active ultrafine powder is:

[0042] Siliceous slag, limestone, slag and sodium sulfate are weighed in a weight ratio of 3:1:2:1 for later use; the slag in the above weight proportion is poured into a crusher and crushed to a particle size of less than 5 mm; then, the slag is mixed with siliceous slag, limestone and sodium sulfate in the above weight ratio and poured into a ball mill together; after ball milling for 30 minutes, a highly active ultrafine powder is obtained; the crusher model is a 5E-JC100×60 jaw crusher, and the ball mill model is an SM-500 ball mill.

[0043] S2, modifying the highly active ultrafine powder with N-phenyl-3-aminopropyltrimethoxysilane to prepare heat-resistant modified micropowder;

[0044] Wherein, the preparation steps of heat-resistant modified micropowder are:

[0045] Step 1, weigh 12g of high-activity ultrafine powder dried in a vacuum drying oven at 120°C for 2h, disperse it in 200mL of 90% ethanol aqueous solution, ultrasonically disperse it at a frequency of 26kHz for 30min, then drop 0.2g of N-phenyl-3-aminopropyltrimethoxysilane, stir it at a speed of 500r / min for 5min, and record the result as the component to be reacted;

[0046] Step 2: Place the components to be reacted in a constant temperature water bath at 80°C and stir at a speed of 300r / min for 1 hour. After the reaction is completed, place them in a vacuum drying oven at 80°C and dry them for 24 hours to obtain heat-resistant modified micropowder.

[0047] S3, firstly etching the surface of the high-activity ultrafine powder with an alkali solution, and then modifying the surface of the high-activity ultrafine powder with a silane coupling agent KH-570 to prepare an activated modified micropowder;

[0048] Wherein, the preparation steps of activated modified micropowder are:

[0049] Step A, immersing the highly active ultrafine powder in a sodium hydroxide solution with a concentration of 5 mol / L for 24 hours for etching, filtering out the filtrate, washing with deionized water and anhydrous ethanol three times respectively, filtering and drying in a vacuum drying oven at 105° C. for 2 hours, and the obtained powder is recorded as etching powder;

[0050] Step B: Mix 200 mL of deionized water and 300 mL of methanol, add 3 g of silane coupling agent KH-570, stir at 300 r / min for 20 min, add 25 g of etching powder, stir at 200 r / min at room temperature for 12 h, filter and remove the filtrate, wash with deionized water and anhydrous ethanol three times each, place in a vacuum drying oven at 105°C and dry for 2 h to obtain the activated modified powder.

[0051] S4, then using the sodium aluminate solution as a raw material to prepare ultrafine aluminum hydroxide powder;

[0052] Wherein, the preparation steps of ultrafine aluminum hydroxide powder are:

[0053] Step I: Add 15 g of lime to 200 mL of 10% sodium aluminate solution, stir at 400 r / min for 30 min, let stand at 97 ° C for 4 h, filter and record as refined solution, heat the refined solution to 20 ° C and simmer at 230 m 3 / h of aeration, and then stop aeration until the pH value of the refined solution reaches 8.5. The solution is allowed to stand for 24 hours and the obtained product is recorded as high-activity seed crystals;

[0054] Step II: Add 5 g of highly active seed crystals to 20 mL of refined solution heated to 55°C, stir and decompose at a speed of 220 r / min for 2 hours, then add 80 mL of refined solution and heat to 55°C, continue stirring at the original speed for 8 hours, and then filter, wash the filter cake with deionized water at a temperature of 45°C until it is neutral, and dry it in a vacuum drying oven at 85°C for 2 hours to obtain ultrafine aluminum hydroxide powder.

[0055] S5. Weigh 50 parts by weight of heat-resistant modified micropowder, 50 parts by weight of activated modified micropowder, 30 parts by weight of ultrafine aluminum hydroxide micropowder and 25 parts by weight of composite activator, mix them, place them in a 105°C forced air drying oven and dry them for 2 hours, and the result is recorded as a powder component; wherein the preparation method of the composite activator is to mix quicklime, hemihydrate gypsum, natural gypsum and water glass in equal weight ratios.

[0056] S6. Pour the powder components into a vibration mill at a material-to-ball ratio of 1:12 and grind them at a filling rate of 40% for 10 minutes. The obtained powder is a highly active ultrafine powder after passing through a 400-mesh sieve.

[0057] A high-activity ultrafine powder is prepared by a high-activity ultrafine powder preparation method.

[0058] Example 2

[0059] A method for preparing a highly active ultrafine powder in this embodiment is as follows:

[0060] S1, mixing siliceous slag, limestone, slag and sodium sulfate in a certain proportion and grinding them to prepare a highly active ultrafine powder;

[0061] Wherein, the preparation method of highly active ultrafine powder is:

[0062] Siliceous slag, limestone, slag and sodium sulfate are weighed in a weight ratio of 3:1:2:1 for later use; the slag in the above weight proportion is poured into a crusher and crushed to a particle size of less than 5 mm; then, the slag is mixed with siliceous slag, limestone and sodium sulfate in the above weight ratio and poured into a ball mill together; after ball milling for 30 minutes, a highly active ultrafine powder is obtained; the crusher model is a 5E-JC100×60 jaw crusher, and the ball mill model is an SM-500 ball mill.

[0063] S2, modifying the highly active ultrafine powder with N-phenyl-3-aminopropyltrimethoxysilane to prepare heat-resistant modified micropowder;

[0064] Wherein, the preparation steps of heat-resistant modified micropowder are:

[0065] Step 1, weigh 15g of high-activity ultrafine powder placed in a vacuum drying oven at 120°C and dried for 2h, disperse it in 200mL of 90% ethanol aqueous solution, ultrasonically disperse it at a frequency of 26kHz for 30min, then drop 0.2g of N-phenyl-3-aminopropyltrimethoxysilane, stir it at a speed of 500r / min for 5min, and record the result as the component to be reacted;

[0066] Step 2: Place the components to be reacted in a constant temperature water bath at 80°C and stir at a speed of 300r / min for 1 hour. After the reaction is completed, place them in a vacuum drying oven at 80°C and dry them for 24 hours to obtain heat-resistant modified micropowder.

[0067] S3, firstly etching the surface of the high-activity ultrafine powder with an alkali solution, and then modifying the surface of the high-activity ultrafine powder with a silane coupling agent KH-570 to prepare an activated modified micropowder;

[0068] Wherein, the preparation steps of activated modified micropowder are:

[0069] Step A, immersing the highly active ultrafine powder in a sodium hydroxide solution with a concentration of 5 mol / L for 48 hours for etching, filtering out the filtrate, washing with deionized water and anhydrous ethanol three times respectively, filtering and drying in a vacuum drying oven at 105° C. for 2 hours, and the obtained powder is recorded as etching powder;

[0070] Step B: After mixing 200 mL of deionized water and 300 mL of methanol, add 4 g of silane coupling agent KH-570, stir at 300 r / min for 20 min, add 30 g of etching powder, stir at 200 r / min at room temperature for 12 h, filter and remove the filtrate, wash with deionized water and anhydrous ethanol three times each, place in a vacuum drying oven at 105°C and dry for 2 h to obtain the activated modified powder.

[0071] S4, then using the sodium aluminate solution as a raw material to prepare ultrafine aluminum hydroxide powder;

[0072] Wherein, the preparation steps of ultrafine aluminum hydroxide powder are:

[0073] Step I: Add 20 g of lime to 200 mL of 10% sodium aluminate solution, stir at 400 r / min for 30 min, let stand at 97 ° C for 4 h, filter and record as refined solution, heat the refined solution to 20 ° C and simmer at 230 m 3 / h of aeration, and then stop aeration until the pH value of the refined solution reaches 10. The solution is allowed to stand for 24 hours and the resulting product is recorded as a high-activity seed crystal;

[0074] Step II: Add 5 g of highly active seed crystals to 20 mL of refined solution heated to 55°C, stir and decompose at a speed of 220 r / min for 2 hours, then add 80 mL of refined solution and heat to 55°C, continue stirring at the original speed for 8 hours, and then filter, wash the filter cake with deionized water at a temperature of 45°C until it is neutral, and dry it in a vacuum drying oven at 85°C for 2 hours to obtain ultrafine aluminum hydroxide powder.

[0075] S5. Weigh 50 parts by weight of heat-resistant modified micropowder, 50 parts by weight of activated modified micropowder, 30 parts by weight of ultrafine aluminum hydroxide micropowder and 25 parts by weight of composite activator, mix them, place them in a 105°C forced air drying oven and dry them for 2 hours, and the result is recorded as a powder component; wherein the preparation method of the composite activator is to mix quicklime, hemihydrate gypsum, natural gypsum and water glass in equal weight ratios.

[0076] S6. Pour the powder components into a vibration mill at a material-to-ball ratio of 1:12 and grind at a filling rate of 40% for 30 minutes. The obtained powder is a highly active ultrafine powder after passing through a 400-mesh sieve.

[0077] A high-activity ultrafine powder is prepared by a high-activity ultrafine powder preparation method.

[0078] Example 3

[0079] A method for preparing a highly active ultrafine powder in this embodiment is as follows:

[0080] S1, mixing siliceous slag, limestone, slag and sodium sulfate in a certain proportion and grinding them to prepare a highly active ultrafine powder;

[0081] Wherein, the preparation method of highly active ultrafine powder is:

[0082] Siliceous slag, limestone, slag and sodium sulfate are weighed in a weight ratio of 3:1:2:1 for later use; the slag in the above weight proportion is poured into a crusher and crushed to a particle size of less than 5 mm; then, the slag is mixed with siliceous slag, limestone and sodium sulfate in the above weight ratio and poured into a ball mill together; after ball milling for 30 minutes, a highly active ultrafine powder is obtained; the crusher model is a 5E-JC100×60 jaw crusher, and the ball mill model is an SM-500 ball mill.

[0083] S2, modifying the highly active ultrafine powder with N-phenyl-3-aminopropyltrimethoxysilane to prepare heat-resistant modified micropowder;

[0084] Wherein, the preparation steps of heat-resistant modified micropowder are:

[0085] Step 1, weigh 14g of high-activity ultrafine powder dried in a vacuum drying oven at 120°C for 2h, disperse it in 200mL of 90% ethanol aqueous solution, ultrasonically disperse it at a frequency of 26kHz for 30min, then drop 0.2g of N-phenyl-3-aminopropyltrimethoxysilane, stir at a speed of 500r / min for 5min, and record the result as the component to be reacted;

[0086] Step 2: Place the components to be reacted in a constant temperature water bath at 80°C and stir at a speed of 300r / min for 1 hour. After the reaction is completed, place them in a vacuum drying oven at 80°C and dry them for 24 hours to obtain heat-resistant modified micropowder.

[0087] S3, firstly etching the surface of the high-activity ultrafine powder with an alkali solution, and then modifying the surface of the high-activity ultrafine powder with a silane coupling agent KH-570 to prepare an activated modified micropowder;

[0088] Wherein, the preparation steps of activated modified micropowder are:

[0089] Step A, immersing the highly active ultrafine powder in a sodium hydroxide solution with a concentration of 5 mol / L for 36 hours for etching, filtering out the filtrate, washing with deionized water and anhydrous ethanol three times respectively, filtering and drying in a vacuum drying oven at 105° C. for 2 hours, and the obtained powder is recorded as etching powder;

[0090] Step B: After mixing 200 mL of deionized water and 300 mL of methanol, add 4 g of silane coupling agent KH-570, stir at 300 r / min for 20 min, add 28 g of etching powder, stir at 200 r / min at room temperature for 12 h, filter and remove the filtrate, wash with deionized water and anhydrous ethanol three times each, place in a vacuum drying oven at 105°C and dry for 2 h to obtain the activated modified powder.

[0091] S4, then using the sodium aluminate solution as a raw material to prepare ultrafine aluminum hydroxide powder;

[0092] Wherein, the preparation steps of ultrafine aluminum hydroxide powder are:

[0093] Step I: Add 18 g of lime to 200 mL of 10% sodium aluminate solution, stir at 400 r / min for 30 min, let stand at 97 ° C for 4 h, filter and record as refined solution, heat the refined solution to 20 ° C and simmer at 230 m 3 / h of aeration, and then stop aeration until the pH value of the refined solution reaches 9. The solution is allowed to stand for 24 hours and the resulting product is recorded as a high-activity seed crystal;

[0094] Step II: Add 5 g of highly active seed crystals to 20 mL of refined solution heated to 55°C, stir and decompose at a speed of 220 r / min for 2 hours, then add 80 mL of refined solution and heat to 55°C, continue stirring at the original speed for 8 hours, and then filter, wash the filter cake with deionized water at a temperature of 45°C until it is neutral, and dry it in a vacuum drying oven at 85°C for 2 hours to obtain ultrafine aluminum hydroxide powder.

[0095] S5. Weigh 50 parts by weight of heat-resistant modified micropowder, 50 parts by weight of activated modified micropowder, 30 parts by weight of ultrafine aluminum hydroxide micropowder and 25 parts by weight of composite activator, mix them, place them in a 105°C forced air drying oven and dry them for 2 hours, and the result is recorded as a powder component; wherein the preparation method of the composite activator is to mix quicklime, hemihydrate gypsum, natural gypsum and water glass in equal weight ratios.

[0096] S6. Pour the powder components into a vibration mill at a material-to-ball ratio of 1:12 and grind at a filling rate of 40% for 20 minutes. The obtained powder is a highly active ultrafine powder after passing through a 400-mesh sieve.

[0097] A high-activity ultrafine powder is prepared by a high-activity ultrafine powder preparation method.

[0098] Comparative Example 1

[0099] The high-activity ultrafine powder and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 1, the high-activity ultrafine powder in Example 1 is replaced with siliceous slag.

[0100] Comparative Example 2

[0101] The high-activity ultrafine powder and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that the high-activity ultrafine powder in Example 1 is replaced with limestone in this comparative example 2.

[0102] Comparative Example 3

[0103] The high-activity ultrafine powder and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 3, the activated modified micropowder in Example 1 is replaced with heat-resistant modified micropowder.

[0104] Comparative Example 4

[0105] The high-activity ultrafine powder and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 4, the heat-resistant modified micropowder in Example 1 is replaced with activated modified micropowder.

[0106] Performance Testing

[0107] The highly active ultrafine powders in Examples 1-3 and Comparative Examples 1-4 are marked as Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, respectively. Then, the performance of Examples 1-3 and Comparative Examples 1-4 is tested. The test methods and test items are as follows:

[0108] 1. The specific surface areas of Examples 1-3 and Comparative Examples 1-4 after grinding for 120 min were tested according to the standard of GB / T8074-2008 "Determination of specific surface area of ​​cement - Blaine method", and the obtained data are recorded in the following table;

[0109] 2. The mechanical properties of Examples 1-3 and Comparative Examples 1-4 were tested with reference to the standard of GB / T17671-1999 "Test Method for Strength of Cement Mortar", and the obtained data are recorded in the following table;

[0110]

[0111]

[0112] It can be seen from the data in the above table that the specific surface areas of the high-activity ultrafine powders in Examples 1-3 are all higher than those in Comparative Examples 1-4, indicating that the high-activity ultrafine powders prepared by compounding multiple components in the present invention can obtain higher activity after modification by different modifiers; secondly, the flexural strength and compressive strength of the high-activity ultrafine powders in Examples 1-3 are significantly higher than those in Comparative Examples 1-4, indicating that the preparation method in the present invention can improve the mechanical properties of the high-activity ultrafine powders.

[0113] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0114] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing highly active ultrafine powder, characterized in that: The preparation method is: S1, mixing siliceous slag, limestone, slag and modifier in a certain proportion and grinding them to prepare highly active ultrafine powder; S2, modifying the highly active ultrafine powder with N-phenyl-3-aminopropyltrimethoxysilane to prepare heat-resistant modified micropowder; S3, firstly etching the surface of the high-activity ultrafine powder with an alkali solution, and then modifying the surface of the high-activity ultrafine powder with a silane coupling agent KH-570 to prepare an activated modified micropowder; S4, then using the sodium aluminate solution as a raw material to prepare ultrafine aluminum hydroxide powder; S5, weigh 50 parts by weight of heat-resistant modified micropowder, 50 parts by weight of activated modified micropowder, 30 parts by weight of ultrafine aluminum hydroxide micropowder and 25 parts by weight of composite activator, mix them, place them in a blast drying oven at 105° C. and dry them for 2 hours, and record the result as powder component; S6. Pour the powder components into a vibration mill at a material-to-ball ratio of 1:12 and grind for 10-30 minutes. The obtained powder is a highly active ultrafine powder after passing through a 400-mesh sieve.

2. The method for preparing a highly active ultrafine powder according to claim 1, characterized in that: The preparation method of high activity ultrafine powder in S1 is: Siliceous slag, limestone, slag and modifier are weighed in a weight ratio of 3:1:2:1 for later use. The slag in the above weight proportion is poured into a crusher and crushed to a particle size of less than 5 mm. Then, it is mixed with siliceous slag, limestone and modifier in the above weight ratio and poured into a ball mill together. After ball milling for 30 minutes, the highly active ultrafine powder is obtained.

3. The method for preparing a highly active ultrafine powder according to claim 1, characterized in that: The preparation steps of the heat-resistant modified micropowder in S2 are: Step 1, weigh 12-15g of the dried high-activity ultrafine powder and disperse it in 200mL of ethanol aqueous solution, add 0.2g of N-phenyl-3-aminopropyltrimethoxysilane dropwise after ultrasonic treatment, and stir and disperse to obtain the component to be reacted; Step 2: Place the components to be reacted in a constant temperature water bath at 80°C and stir to react for 1 hour. After the reaction is completed, place them in a vacuum drying oven at 80°C and dry them for 24 hours to obtain heat-resistant modified micropowder.

4. The method for preparing a highly active ultrafine powder according to claim 3, characterized in that: The drying method in step 1 is to place the mixture in a vacuum drying oven at 120° C. and dry it for 2 h. The volume fraction of the ethanol aqueous solution in step 1 is 90%. The ultrasonic treatment method in step 1 is to perform ultrasonic dispersion at a frequency of 26 kHz for 30 min. The stirring and dispersion method in step 1 is to stir at a speed of 500 r / min for 5 min. The stirring reaction speed in step 2 is 300 r / min.

5. The method for preparing a highly active ultrafine powder according to claim 1, characterized in that: The preparation steps of the activated modified micropowder in S3 are: Step A, immersing the highly active ultrafine powder in a sodium hydroxide solution for 24-48 hours for etching, filtering out the filtrate, washing with deionized water and anhydrous ethanol three times respectively, filtering and drying, and the obtained powder is recorded as etching micropowder; Step B: Mix 200 mL of deionized water and 300 mL of methanol, add 3-4 g of silane coupling agent KH-570, stir for hydrolysis, add 25-30 g of etching powder, stir and react at room temperature for 12 hours, filter to remove the filtrate, wash with deionized water and anhydrous ethanol three times each, and dry to obtain the activated modified powder.

6. The method for preparing a highly active ultrafine powder according to claim 5, characterized in that: The concentration of the sodium hydroxide solution in step A is 5 mol / L, the drying operation method in step A is to place it in a vacuum drying oven at 105° C. and dry it for 2 hours, the stirring and hydrolysis operation method in step B is to stir at a speed of 300 r / min for 20 minutes, the stirring reaction speed in step B is 200 r / min, and the drying operation method in step B is to place it in a vacuum drying oven at 105° C. and dry it for 2 hours.

7. The method for preparing a highly active ultrafine powder according to claim 1, characterized in that: The preparation steps of the ultrafine aluminum hydroxide powder in S4 are: Step I: Add 15-20 g of lime to 200 mL of sodium aluminate solution, stir thoroughly, let stand at 97 ° C for 4 hours, filter and record as refined solution, heat the refined solution to 20 ° C and simmer at 230 m 3 / h ventilation of carbon dioxide gas until the pH value of the refined solution reaches 8.5-10, then stop ventilation, and let it stand for 24h to age, the obtained product is recorded as high-activity seed crystal; Step II: Add 5 g of highly active seed crystals to 20 mL of refined solution heated to 55°C, stir and decompose at a speed of 220 r / min for 2 hours, then add 80 mL of refined solution and heat to 55°C, continue stirring at the original speed for 8 hours, then filter, wash the filter cake with deionized water at a temperature of 45°C until it is neutral, and obtain ultrafine aluminum hydroxide powder after drying.

8. The method for preparing a highly active ultrafine powder according to claim 7, characterized in that: The mass fraction of the sodium aluminate solution in step I and step II is 10%. The operation method of fully stirring in step I is stirring at a speed of 400 r / min for 30 minutes. The operation method of drying in step II is placing in a vacuum drying oven at 85° C. for 2 hours.

9. The method for preparing a highly active ultrafine powder according to claim 1, characterized in that: The composite activator in S5 is prepared by mixing quicklime, hemihydrate gypsum, natural gypsum and water glass in equal weight ratios. The filling rate of the vibration mill in the grinding process of S6 is 40%.

10. A highly active ultrafine powder, characterized in that: The invention is prepared by the method for preparing a high-activity ultrafine powder according to any one of claims 1 to 9.